A teljesítményértékelés kapcsolata a humán erőforrás menedzsment különböző területeivel - Lepp Katalin (Taylor : gazdálkodás- és szervezéstudományi folyóirat, 2014)
Performance appraisal is an activity that provides support to different areas of human resource management in order to contribute to the economic profitability of the companies. The employees are in need of regular feedback concerning their work, its quality and the behaviour at the workplace because the profitability of their work performance can be evaluated according to the mentioned factors. Performance appraisal is considered to be an important event in the life of the employees because it is the frame to evaluate their work; to determine the tasks to be done; to determine the purpose of the whole activity; to decide about a possible pay raise; to discuss about the future career opportunities and to have a satisfaction survey concerning the employees. A well prepared performance appraisal can be considered as a base for the whole process of human resource management from the recruitment of workers through retention, carrier management, training and motivation to the discharge. This study examines the interrelation between performance appraisal and the functions of human resource management.